MushMagic: Mushroom Ordering Application - Guthangasolam, Jivitha; SALAMAT, MOHAMAD AIZI (Applied Information Technology And Computer Science, 2025)
At AGS PRO Enterprise in Kampung Pengkalan Lebai Man, Kedah, the conventional method of ordering mushrooms presents problems for both customer satisfaction and efficiency. Our proposal presents "MushMagic," a cutting-edge online ordering tool, as a solution to this. Our goal is to completely transform the mushroom purchasing experience by giving consumers an easy-to-use platform on which to browse, order, and monitor their purchases. To improve customer engagement and simplify inventory management, an effective digital system has to be integrated. Important results show a significant improvement in order fulfillment, inventory accuracy, and customer happiness. The discussion highlights how MushMagic has completely changed the way AGS PRO Enterprise operates and offers potential strategies for future development and improvement in the age of digital media. To address evolving customer requirements along with business trends, future development will include ongoing modification and growth.